1997
DOI: 10.1007/bf01271297
|View full text |Cite
|
Sign up to set email alerts
|

Regional distribution of specific high affinity binding sites for 3H-imipramine and 3H-paroxetine in human brain

Abstract: The binding of 3H-paroxetine and 3H-imipramine has been compared in 17 different regions of 12 human control brains. Our findings reveal that the regional distribution is similar for both radioligands and their bindings tend to be parallel in the brain. The highest binding site density was found in basal ganglia (hypothalamus Bmax 780 +/- 102 fmol/mg protein for 3H-imipramine binding and Bmax 515 approximately 83 for 3H-paroxetine binding). The lowest values were found in cortical areas (cingulate cortex 191 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Several postmortem studies have documented the distribution of SERT cells in the human brain (Cortes et al, 1988;Laruelle et al, 1988;Backstrom et al, 1989;Plenge et al, 1990;Rosel et al, 1997). High SERT density is observed at the level of the midbrain nuclei, reflecting the presence of SERT on both the 5-HT cell body (raphe nuclei) and on terminals of the dense 5-HT innervation of the adjacent structures (substantia nigra, nucleus interpeduncularis, locus ceruleus, nucleus nervi Br]5-bromo-6-nitroquipazine have been evaluated as potential PET or SPECT radiotracers and found to be unsuitable due to high lipophilicity and/or high nonspecific binding (Hashimoto et al, 1987;Lasne et al, 1989;Dannals et al, 1990;Hume et al, 1991;Nelson et al, 1991;Livni et al, 1994;Scheffel et al, 1994;Jagust et al, 1996;Bergstrom et al, 1997;Smith et al, 1997;Zea-Ponce et al, 1997;Lundkvist et al, 1999).…”
mentioning
confidence: 99%
“…Several postmortem studies have documented the distribution of SERT cells in the human brain (Cortes et al, 1988;Laruelle et al, 1988;Backstrom et al, 1989;Plenge et al, 1990;Rosel et al, 1997). High SERT density is observed at the level of the midbrain nuclei, reflecting the presence of SERT on both the 5-HT cell body (raphe nuclei) and on terminals of the dense 5-HT innervation of the adjacent structures (substantia nigra, nucleus interpeduncularis, locus ceruleus, nucleus nervi Br]5-bromo-6-nitroquipazine have been evaluated as potential PET or SPECT radiotracers and found to be unsuitable due to high lipophilicity and/or high nonspecific binding (Hashimoto et al, 1987;Lasne et al, 1989;Dannals et al, 1990;Hume et al, 1991;Nelson et al, 1991;Livni et al, 1994;Scheffel et al, 1994;Jagust et al, 1996;Bergstrom et al, 1997;Smith et al, 1997;Zea-Ponce et al, 1997;Lundkvist et al, 1999).…”
mentioning
confidence: 99%
“…The density of [3H]paroxetine and [3H]imipramine binding sites defined with 5-HT as displacing agent was similarly distributed among brain regions studied, with a higher Bmax in hypothalamus (Cumming and Gjedde, 1993 Rosel et al, 1997a) and lower values in frontal cortex (B~ickstrom et al, 1989;Plenge et al, 1990). These results are similar in depressed suicides and in controls.…”
Section: Discussionmentioning
confidence: 95%
“…25 Three versions of the binding potential were then computed from the V T values: 25 Here the cerebellum gray matter was used as the reference region. Previous studies reported extremely low 2,3 or low 4,5,26 SERT density in the cerebellum.…”
Section: Kinetic Modelingmentioning
confidence: 99%
“…An automated blood counting system (PBS-101; Veenstra Instruments, Joure, The Netherlands) was used to measure the radioactivity in whole blood during the first 7 minutes, with blood withdrawn continuously at 4 mL/min. Thereafter, 15 samples (1 to 6 mL) were collected manually at 3,5,7,10,15,20,25,30,40,50,60,75,90,105, and 120 minutes after tracer administration. For each sample, plasma was obtained by refrigerated centrifugation (2930 g at 41C for 5 minutes).…”
Section: Input Function Measurementmentioning
confidence: 99%
See 1 more Smart Citation